Thematic Analysis Of Accreditation And Iso 21001 At Higher Education Institution In Batam - Efendi, Yarsi; Hapsari, Ratna F; Yusup, Rhisna Rachmawati (International Journal of Management, Innovation, and Education, 2025)
Higher education in Indonesia, particularly in Batam, must adapt to global demands to enhance quality through the implementation of the international standard ISO 21001:2018. This research aims to explore the gap between national accreditation and the understanding and application of ISO 21001:2018 in higher education institutions. Using a literature review approach, the study identifies the need for a deeper understanding of the standard, as well as the challenges faced by institutions, such as resistance to change and resource limitations. The findings indicate that, despite significant potential for improving educational quality through ISO 21001:2018, many institutions have yet to prioritise its implementation. Therefore, socialisation, training, and government support are crucial to ensure the effective application of this standard to enhance the competitiveness of educational institutions at both regional and international levels